2017
DOI: 10.1016/j.worlddev.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Does Aid Effectiveness Depend on the Quality of Donors?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…Some studies have also found that the effect of foreign aid on economic growth is non‐linear and depends on several macroeconomic and institutional indicators. Some papers show that aid is effective under some conditions: good governance (Burnside & Dollar, 2000, 2004; Ikhide, 2004), vulnerability of the recipient country (Chauvet & Guillaumont, 2004; Guillaumont & Chauvet, 2001), export price shocks (Collier & Dehn, 2001), regulatory burden (Harms & Lutz, 2003) and the quality of donors (Minasyan, Nunnenkamp, & Richert, 2017). Other studies have shown that there is a decreasing marginal return to aid (Dalgaard & Hansen, 2001; Gomanee et al., 2003; Guillaumont & Guillaumont‐Jeanneney, 2006a; Lensink & White, 2001).…”
Section: Brief Review Of the Literaturementioning
confidence: 99%
“…Some studies have also found that the effect of foreign aid on economic growth is non‐linear and depends on several macroeconomic and institutional indicators. Some papers show that aid is effective under some conditions: good governance (Burnside & Dollar, 2000, 2004; Ikhide, 2004), vulnerability of the recipient country (Chauvet & Guillaumont, 2004; Guillaumont & Chauvet, 2001), export price shocks (Collier & Dehn, 2001), regulatory burden (Harms & Lutz, 2003) and the quality of donors (Minasyan, Nunnenkamp, & Richert, 2017). Other studies have shown that there is a decreasing marginal return to aid (Dalgaard & Hansen, 2001; Gomanee et al., 2003; Guillaumont & Guillaumont‐Jeanneney, 2006a; Lensink & White, 2001).…”
Section: Brief Review Of the Literaturementioning
confidence: 99%
“…Aid is also often tied, calling for unnecessary (mega) project proliferation, misallocation of resources and neglect of the potential of smaller-scale entrepreneurship in raising living standards. While it is known that higher-quality aid from the donor side leads to better development results, it is the smaller recipient countries, all else being equal, which seem to benefit more from high-quality aid than their larger counterparts (Minasyan et al 2016). Other criteria often included in evaluating aid quality include the level of aid channel politicization, selectivity on projects, provision of global public goods and technical efficiency (Gulrajani 2016).…”
Section: Foreign Aid Donor-created Obstacles On Entrepreneurshipmentioning
confidence: 99%
“…For example, Minasyan et al (2017) demonstrate that only qualityadjusted aid leads to increasing GDP per capita in recipient countries. The authors base their findings on the donor performance index of the Center for Global Development.…”
Section: Relevant Literaturementioning
confidence: 99%